Revealing underlying mechanisms affecting electrokinetic remediation of an artificially Cu- and Pb-contaminated loess using the external regulatory system with adsorbent - Hu, Wenle; Cheng, Wen-Chieh; Wen, Shaojie; Kang, Nongbo (Frontiers in Materials, 2022)
Considering extensive metallurgical mining activities in the northwest of China, handling Cu- and Pb-rich wastewater is a challenging task. Inappropriate handling of the Cu- and Pb-rich wastewater can lead to accumulation of Cu and Pb in the surrounding environment, thereby posing a serious threat to human health. Electrokinetic (EK) technology is an increasingly popular alternative to traditional approaches for contaminated soil remediation owing to its high effectiveness and low risk of secondary pollution. This study first proposed an external regulatory system with the adsorbent (ERSA) and investigated the effect of electrode type, ERSA, and cation exchange membrane (CEM) on the EK remediation of an artificially Cu- and Pb-contaminated loess. An EK reactor incorporating ERSA was applied to the EK experiments to circulate the electrolyte, not only making pH surrounding the cathode lower, but also preventing the formation of precipitation. The electrokinetic geosynthetics electrode released H+ and OH− faster and promoted their migration toward the specimen. However, because of the faster precipitation near the cathode, the boost in the remediation efficiency was hindered. Furthermore, considering the ERSA use, a decrease in soil pH near the cathode reduced the precipitation, thereby enhancing the EK remediation efficiency. In contrast, the use of CEM lowered the soil pH, increased the soil electrical conductivity (EC) and electric current, and aggravated the electroosmotic flow. The Cu remediation efficiency using the modified EK reactor was largely lifted to 85.52%, while the Pb remediation efficiency increased to 75.51%. These results shed light on an enhancement on the EK remediation efficiency and the potential of applying the modified EK reactor to remedy Cu- and Pb-rich water bodies.